Inflammatory regenerative processes dynamics with corneal ulcer against the background of usage of blood autologous mononuclear leukocyte - I. V. Zapuskalov; O. I. Krivosheina; N. A. Levchenko (Бюллетень сибирской медицины, 2011)
In the experiment in vivo the mechanisms of the development of inflammatory regenerative processes with corneal ulcer against the background of the instillations of blood autologous mononuclear leukocyte and traditional pharmacotherapy are studied. It is determined that against the background of the use of blood autologous mononuclear leukocyte the duration and the intensity of inflammation reduce and the clearance of ulcer defect from necrotic mass accelerates. The instillations of blood autologous mononuclear leukocyte against the background of traditional pharmacotherapy of experimental corneal ulcer stimulate fast change of cell phases in the inflammation center and activate the process of regeneration of damaged cornea structures.